In-utero idiopathic ductal constriction: a prenatal manifestation of Alagille and Williams syndrome arteriopathy. (November 2018) - Srinivasan, Shardha; Howley, Lisa; Cuneo, Bettina; Chatfield, Kathryn
Abstract Objective Williams and Alagille syndromes are genetic disorders associated with pathologic arterial narrowing. We hypothesized that fetal idiopathic ductus arteriosus (DA) constriction may represent a prenatal manifestation of the arteriopathy associated with these syndromes. Methods Multi-institutional case series review of the pre- and postnatal medical records, echocardiograms, and genetic test results of fetuses presenting with idiopathic DA constriction. Results We identified four cases of idiopathic fetal DA constriction at 21–36 weeks of gestation. All had right ventricular hypertension, dilation, hypertrophy, and dysfunction and either DA constriction or absence. All demonstrated progressive peripheral pulmonary artery stenosis after birth. Three met clinical diagnostic criteria for Alagille syndrome; two tested had confirmatoryJAG1 mutations. One also developed supravalvar aortic stenosis after birth and was positive for 7q11.23 deletion (Williams syndrome). Conclusion This is the first case series to suggest that idiopathic fetal DA constriction may be a prenatal manifestation of genetic arteriopathy.